Population immunity to measles in Canada using Canadian Health Measures survey data – A Canadian Immunization Research Network (CIRN) study. Issue 23 (20th May 2022) - Osman, Selma; Crowcroft, Natasha; McLachlan, Elizabeth; Hatchette, Todd; Perez-Iratxeta, Carol; Joh, Eugene; Wright, James; Halperin, Scott A.; Deeks, Shelley; Wilson, Sarah; Buchan, Sarah; Ward, Brian; et al.
Highlights: Assessed population immunity to measles in Canada using specimens collected through the Canadian Health Measures Survey. Overall, 90.0% (95% CI: 88.2, 91.9) of samples were positive. Individuals aged 19 and under who were born in Canada were less susceptible compared to those born outside Canada. Individual aged 20 and over born in Canada were more susceptible compared to those born outside Canada. Abstract: We aimed to determine population immunity to measles in Canada, and to assess the risk of future outbreaks. We tested 11, 176 sera from Cycles 2 (2009–2011) and 3 (2011–2013) cohorts from the biobank of Statistics Canada's Canadian Health Measures Survey (CHMS) using the BioPlex 2220 MMRV IgG assay. We then tested all BioPlex negative and equivocal samples using a more sensitive Plaque Reduction Neutralization Test (PRNT). We determined the weighted proportion of positive, equivocal, and negative samples by age, sex, region and whether individuals were born in Canada. We found that 90.0% (95% confidence interval (CI): 88.2, 91.9) of samples were positive, 4.5% (95% CI: 3.4, 5.5) were equivocal and 5.5% (95% CI: 4.3, 6.7) were negative. Individuals in the 12–19 year age band had the lowest proportion positive at 78.7% (95% CI: 74.2, 83.2) and the highest proportion of positive samples was found in those 60–79 years (99.6%, 95% CI: 99.3, 99.9). Seropositivity was consistently <90% across a broad range of pediatric and adult age bands (6–39 years). We found that a slightly higher proportion of females were positive (91.9%, 95% CI: 90.1, 93.6) compared to males (88.3%, 95% CI: 85.8, 90.7). When taking into account interaction between age and born in Canada status, we found individuals born in Canada aged 19 and under were less susceptible (OR = 0.6 (95% CI: 0.4, 0.95)) compared to those born outside Canada whereas, those aged 20 and over were more susceptible (OR = 1.7 (95% CI: 1.1, 2.8)). Our findings indicate that measles immunity in Canada is below the 95% immunity threshold required to sustain measles elimination, underscoring the importance of maintaining high vaccine coverage to prevent future measles outbreaks and sustain Canada's elimination status.